2010
DOI: 10.1021/ic101038z
|View full text |Cite
|
Sign up to set email alerts
|

Cyanocarbanion-Based Spin-Crossover Materials: Photocrystallographic and Photomagnetic Studies of a New Iron(II) Neutral Chain

Abstract: A new iron(II) chain of formula [Fe(abpt)(2)(tcpd)] [1; (tcpd)(2-) = [C(10)N(6)](2-) = (C[C(CN)(2)](3))(2-) = 2-dicyanomethylene-1,1,3,3-tetracyanopropanediide anion, abpt = 4-amino-3,5-bis(pyridin-2-yl)-1,2,4-triazole] has been synthesized and characterized by IR spectroscopy, detailed variable-temperature single-crystal X-ray diffraction, magnetic and photomagnetic measurements. The crystal structure determination of 1 reveals a one-dimensional structural architecture in which the (tcpd)(2-) cyanocarbanion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 78 publications
1
30
0
Order By: Relevance
“…Noticeably, numerous examples of 1D chains made of flexible single bridge spacers systematically reveal a gradual spin conversion as noted for 1,2-bis(4-pyridyl)etha(e)ne [308], 4,4’-bpy [309310], substituted triazine/pyrimidine [307,311313], pyrazine [314], dca [315] and tcpd anions [316]. Some other very interesting 1D chains were recently prepared by Weber et al using tetradentate Schiff bases allowing them to set up a N 4 O 2 core and to observe a variety of magnetic behavior including gradual, hysteretic, complete, incomplete and even double-step spin conversions [317324].…”
Section: Reviewmentioning
confidence: 99%
“…Noticeably, numerous examples of 1D chains made of flexible single bridge spacers systematically reveal a gradual spin conversion as noted for 1,2-bis(4-pyridyl)etha(e)ne [308], 4,4’-bpy [309310], substituted triazine/pyrimidine [307,311313], pyrazine [314], dca [315] and tcpd anions [316]. Some other very interesting 1D chains were recently prepared by Weber et al using tetradentate Schiff bases allowing them to set up a N 4 O 2 core and to observe a variety of magnetic behavior including gradual, hysteretic, complete, incomplete and even double-step spin conversions [317324].…”
Section: Reviewmentioning
confidence: 99%
“…Taking into account the crucial role of these anionic ligands, we are interested in using them in combination with other chelating or bridging neutral co-ligands such as the aromatic N-containing ligands to explore the role of their structural and electronic characteristics in the field of molecular materials including switchable materials exhibiting magnetic bistability [7][8][9][10][11][12][13], as in the intriguing derivative [Cu(bpym)(tcnoet) 2 ].H 2 O (bpym = 2,2'-bipyrimidine; (tcnoet) -= 1,1,3,3-tetracyano-2-ethoxypropenide) that displays a zigzag infinite chain with an unusual magnetic transition and reversible thermochromism [13]. Experimental and theoretical studies revealed that both magnetic and thermochromic transitions are induced by several structural and electronic effects such as the flexibility of the cyanocarbanion ligand, the rigidity and the bis-chelating coordination mode of the bpym ligand and the dynamic Jahn-Teller effect of the Cu(II) metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of incomplete and smooth SCO transition is typical of chain compounds, since when the metallic centers are connected, the transition of one of them exerts a chemical pressure on the bridging ligands that hampers the transition of the neighboring metal centers [45][46][47].…”
Section: Of 15mentioning
confidence: 99%